Analisis Kinerja Organisasi Pengelola Zakat Dengan Pendekatan Indeks Zakat Nasional Di Kota Kediri - Hanafil Haq Aninda; Zuraidah (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2021)
To determine the performance and condition of Zakat Management Organizations (OPZ) in Indonesia, the government formulated the National Zakat Index (IZN). IZN is a measuring tool created to evaluate the development of zakat at the national and regional levels. This is what encourages researchers to research the performance of OPZ in Kediri City and the contribution of ZIS in building the economy and community welfare. The puRp. ose of this study is to determine the performance of OPZ from the dimensions of macro, micro, and the value of their performance. While the type of research used is descriptive quantitative research using interviews, documentation, and questionnaires as data collection methods. Interviews and documentation were conducted to collect data regarding; 1) OPZ performance value based on IZN, 2) OPZ performance value based on macro dimension, 3) OPZ performance value based on micro dimension. Meanwhile, the questionnaire was conducted to collect data regarding; 1) OPZ performance value based on IZN and 2) OPZ performance value based on micro dimension. This study concludes that the performance of OPZ in Kediri City in 2017 is quite good with an index value of 0.58, wherefrom the macro dimension the support from the city government and the community is not good, but from the micro dimensions of the institution's performance and the impact of zakat on mustahik conditions, it has an influence which is quite good. So, there is a need for support from the government so that the existence of OPZ can encourage the creation of better performance and the public is expected to be more aware of zakat so that the distribution of ZIS funds can be carried out properly so that mustahik can feel the benefits.